(untitled) (The Peerian Journal, 2025)
Psychological resilience is a critical factor influencing the performance of football goalkeepers during matches. This study explores the relationship between goalkeepers’ mental toughness, stress management and their overall effectiveness on the field. By analyzing various psychological components such as concentration, emotional control and confidence, the research highlights how resilient goalkeepers are better equipped to handle high-pressure situations, recover from mistakes quickly and maintain consistent performance throughout the game. The findings suggest that targeted psychological training can significantly enhance a goalkeeper’s ability to perform under stress, ultimately contributing to improved match outcomes.